RANCANG BANGUN ALGORITMA KONVERSI SUARA BERBAHASA INDONESIA MENJADI TEKS LATIN BERBAHASA SASAK MENGGUNAKAN METODE DICTIONARY BASED - Shabrina, Marwati Maryam; Aranta, Arik; Irmawati, Budi (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2024)
As time goes by, the use of the Sasak language among the people of Lombok is decreasing. In fact, the Sasak language is the identity of the island of Lombok which needs to be preserved as a heritage for the younger generation. The increasingly rapid development of technology has encouraged the emergence of innovation in creating various inventions that can facilitate human activities. One innovation that can be developed is speech to text technology. This technology can recognize human voices and then convert them into text. This is of interest to the author in designing a system that implements Google’s speech to text API to translate Indonesian words or sentences into Sasak. The translation from Indonesian to Sasak was carried out by applying a dictionary based system to produce an appropriate translation. The testing process was carried out by translating 25 sentences taken from the Sasak-Indonesian Dictionary and consisting of 117 words. In this research, there were two stages of testing carried out. The first test was carried out to determine the accuracy of the results of the Indonesian translation into Sasak using the dictionary based method. The second test was carried out to determine the accuracy of the Google Speech API in recognizing voice input and then converting it into text. From the first test, the system accuracy results in translating Indonesian to Sasak using the dictionary based method were 100% and the error rate was 0%. Meanwhile, from the second test, the results showed that the system could implement the Google Speech API to translate Indonesian words or sentences into Sasak with an accuracy of 99.14%.